Validity of Gift Deed After the Donor's Death in the Perspective of Islamic Law (Analysis of Decision No. 09/Pdt.G/2023/PN.Bkl) - Muhammad Yakup; Kukuh Muljo Rahardjo; Tahegga Primananda Alfath (Al-Huquq: Journal of Indonesian Islamic Economic Law, 2026)
This study examines the legal validity of a gift deed (akta hibah) executed under alleged donor incapacity, as reflected in Decision No. 09/Pdt.G/2023/PN.Bkl of the Bangkalan District Court. Gift Deed No. 9 dated 7 April 2021 is disputed on the ground that the donor was critically ill and unable to freely express legal consent at signing. Using a normative legal research methodology with statutory, case, and conceptual approaches, this study addresses three questions: (1) the legal standing of a non-heir plaintiff in a gift deed annulment dispute; (2) the court's judicial reasoning; and (3) the validity of the deed under Islamic civil law. The findings reveal that a non-heir plaintiff may establish legal standing by demonstrating direct harm through defective consent under Article 1320 of the Civil Code or tortious liability under Article 1365. The court legitimately invoked ius curia novit and its ex officio authority to integrate civil law requirements with Islamic legal standards on donor capacity. Under Islamic civil law, the deed constitutes an 'aqd fasid (defective agreement) because the donor failed to satisfy the 'aqil (sound mind) criterion under Article 210 of the Compilation of Islamic Law corresponding to a voidable agreement (vernietigbaar) under Articles 1321 and 1449 of the Civil Code. Annulment of the deed restores legal order in estate management and safeguards heirs' rights under both Indonesian positive law and Islamic law.